Effects of proximal femoral nail antirotation (PFNA) implant on the stress distribution of the femur - a finite element study - Loh, Christopher Meng Keat (Nanyang Technological University, 2021)
Hip fracture also known as femur fracture, is one of the most common types of injury experienced by the aging population. A hip fracture generally occurs in the proximal femur which is known as a proximal femoral fracture. One of the main contributing factors for hip fracture is osteoporosis as it causes bones to be weaker. There are many classifications of hip fracture, such as femoral-neck fracture, intertrochanteric fracture and subtrochanteric fracture. Femoral-neck fracture and intertrochanteric fracture accounts for 90% of hip fractures. Different surgical implants are needed for different type of hip fracture. The objective of this study is to determine the length of distal extension that can be tolerated by the short proximal femoral nail antirotation (PFNA-II) implant in an intertrochanteric fracture. Finite Element Analysis (FEA) using ABAQUS software was used to perform this study. Models were constructed based on AO classification 31A2.2 with axial load applied to the femoral head. Simulations were done on osteoporotic and normal bone from baseline to 120 mm distal extension. Vertical reaction force and axial stiffness experienced the steepest drop in the region of 30 to 50 mm distal extension. The side of proximal cortical shaft showed to be reaching plastic deformation for distal extension larger than 40 mm. The results obtained may suggest that the length of distal extension that can be tolerated by the short PFNA-II to be in the region of 30 to 50 mm.